2020
DOI: 10.1111/jfbc.13426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti‐aging and antioxidant action of Ananas sativa and Moringa oleifera in a fruit fly model organism

Abstract: aging is an inevitable biological complex process. It involves the gradual loss of cellular vitality due to accumulative damage to cellular macromolecules by reactive oxygen species (ROS). These ROS are highly implicated in health, disease, and lifespan. The biochemical pathways involved in the aging process are highly influenced by both exogenous (environmental factors) and endogenous stress factors. These cellular processes are the same in most organisms including the fruit fly, nematode, yeast, mammalian ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In the meantime, a large number of studies indicated that M. oleifera also possessed anti-aging properties. For instance, M. oleifera leaf extracts displayed anti-aging activity by improving oxidative stress resistance and nutrient-sensing pathways ( 10 ), extending the life span, and improving stress tolerance of Caenorhabditis elegans ( 11 ). Moreover, it was also found that the M. oleifera leaf extracts observably decreased age-related neurodegeneration in the old treated rat model ( 12 ), and its cream restored skin vitality and reduced skin aging ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, a large number of studies indicated that M. oleifera also possessed anti-aging properties. For instance, M. oleifera leaf extracts displayed anti-aging activity by improving oxidative stress resistance and nutrient-sensing pathways ( 10 ), extending the life span, and improving stress tolerance of Caenorhabditis elegans ( 11 ). Moreover, it was also found that the M. oleifera leaf extracts observably decreased age-related neurodegeneration in the old treated rat model ( 12 ), and its cream restored skin vitality and reduced skin aging ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera is one of the natural compounds that contain many active constituents including flavonoids, alkaloids, glycosides, lipids, proteins, carbohydrates, minerals, and vitamins among others [ 45 , 46 ] and belongs to the family of Moringaceae that are distributed widely in many African and Asian countries [ 47 ]. It has been reported to have antioxidative, anti-inflammatory, antimicrobial, bactericidal, hypoglycemic, anti-cancer, anti-aging, and neuroprotective potentials [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. In the field of AD, MO was reported to exert anti-aging, antioxidative, anti-cholinesterase, and neuroprotective activities [ 27 , 49 , 56 , 57 , 58 ] and is safe at higher doses in both rats and mice as its LD50 was more than 6400 mg/kg in mice [ 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to have antioxidative, anti-inflammatory, antimicrobial, bactericidal, hypoglycemic, anti-cancer, anti-aging, and neuroprotective potentials [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. In the field of AD, MO was reported to exert anti-aging, antioxidative, anti-cholinesterase, and neuroprotective activities [ 27 , 49 , 56 , 57 , 58 ] and is safe at higher doses in both rats and mice as its LD50 was more than 6400 mg/kg in mice [ 59 , 60 , 61 ]. Moreover, in our previous study [ 21 ], we found that MO can alleviate homocysteine-induced AD-like pathological changes including Aβ production, Tau hyperphosphorylation, and neurodegeneration via decreasing BACE1, GSK-3β, CDK5, CaMKII, increasing PP2A activities, and improving oxidative stress and cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is thought to be an inevitable biological process, which leads to various diseases including the loss of reproduction and regeneration (Ajagun‐Ogunleye & Ebuehi, 2020). Many studies have shown that ROS are concerned with major processes related to aging, like telomere shortening and autophagy (Lennicke & Cocheme, 2020).…”
Section: Introductionmentioning
confidence: 99%